Predictors of treatment failure, time to switch and reasons for switching to second line antiretroviral therapy in HIV infected children receiving first line anti-retroviral therapy at a Tertiary Care Hospital in Ethiopia - Gelila Solomon Haile; Alemseged Beyene Berha (BMC, 2019)
Abstract Background Treatment failure and delay in switching to second line regimen are major concerns in the treatment of HIV infected children in a resource limited setting. The aim of this study was to determine the prevalence and predictors of first line antiretroviral therapy (ART) regimen failure, reasons and time taken to switch to second line antiretroviral (ARV) medications after treatment failure among HIV-infected children. Methods A retrospective cohort study was conducted February 2003 to May 2018 in HIV-clinic at Tikur Anbessa Specialized Hospital (TASH), Ethiopia. All HIV infected children ≤15 years of age and who were taking first line ART for at least 6 months were included. Data abstraction format was used to collect the data from patients' chart and registry. Binary and multivariable logistic regression statistics were used. Results Out of 318 enrolled HIV-infected children, the prevalence of treatment failure was found to be 22.6% (72/318), among these 37 (51.4%) had only immunologic failure, 6 (8.3%) had only virologic failure and 24 (33.3%) had both clinical and immunological failure. The mean time taken to modify combination antiretroviral therapy (cART) regimen was 12.67 (4.96) weeks after treatment failure was confirmed. WHO Stage 3 and 4 [Adjusted Odds Ratio (AOR), 3.64, 95% CI 1.76-7.56], not having both parents as primary caretakers [AOR, 2.72 95% CI, 1.05-7.06], negative serology of care takers [AOR, 2.69 95% CI, 1.03-7.03], and cART initiation at 11 month or younger were predicting factors of treatment failure. Of the 141 (47.9%) children who had regimen switching or substitution, treatment failure (44.4%) and replacement of stavudine (d4T) (30.8%) were major reasons. Only 6.6% patients had received PMTCT service. Conclusion One fifth of the patients had experienced treatment failure. Advanced WHO stage at baseline, not being taken care of by mother and father, negative sero-status caretakers, and younger age at initiation of cART were the predictors of treatment failure. PMTCT service uptake was very low. There was a significant time gap between detection of treatment failure and initiation of second line cART. Half of the patients encountered regimen switching or substitution of cART due to treatment failure and replacement of stavudine (d4T).